(untitled) (Dhaka University Journal of Science, 2013)
The adsorptive properties of carboxymethyl cellulose (CMC) prepared from sugarcane bagasse (SB) for the removal of methylene blue (MB) from aqueous solution was investigated. Two batches of CMC, CTSB-CMC-B1 and CTSB-CMC-B2, were prepared from chlorite treated sugarcane bagasse (CTSB). The prepared CMCs were characterized by FT-IR spectral analysis. Degree of substitution (DS) value of prepared CMCs was estimated. Batch adsorption experiments show that the adsorption of MB on CMCs reaches equilibrium within 30 minutes. The MB adsorption capacity of CTSB-CMC-B1 and CTSB-CMC-B2 were found to be 652.0 and 369.0 mg g?1, respectively. CMC with the higher DS value (CTSBCMC- B1) shows higher adsorption capacity than the CMC having lower DS value (CTSB-CMC-B2). The uptake of MB was minimum at pH 2 and gradually increases with the increase of pH. From the desorption studies, it was found that large amount of MB was released in strong acidic (pH 3.0) conditions. DOI: http://dx.doi.org/10.3329/dujs.v61i2.17069 Dhaka Univ. J. Sci. 61(2): 193-198, 2013 (July)